Penerapan Konsep 7P sebagai Strategi Pemasaran Perguruan Tinggi untuk Meningkatkan Jumlah Mahasiswa di STAI Darussalam Kunir - Kusumadewi, Riema Afriani; Ramdan, Ahmad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Entering the society era 5.0, competition in various institutions, especially educational institutions, is increasing. The need for education is increasing, especially in higher education, also the increasing population of Indonesia, causing the emergence of many new private universities one of which is STAI Darussalam Kunir. As a new private university, STAI Darussalam Kunir needs to formulate a marketing strategy to increase the number of students by applying the 7 P concept. This study aims to find out marketing strategies, conducted by STAI Darussalam Kunir to increase the number of students. The subjects of this study are the Head of STAI Darussalam Kunir, the admission committee for new students, and the Heads of Study Programs, while the object is the marketing strategy of STAI Darussalam Kunir. The research method used descriptive qualitative methods. The results showed that the marketing strategy carried out by STAI Darussalam Kunir is to apply the concept of the 7 P as follows : Product (Various Service Products offered by STAI Darussalam Kunir ), Price (The price of services offered by STAI Darussalam is relatively cheaper than other campuses), Place (The strategic location of STAI Darussalam Kunir is close to residential housing), Promotion (Using Traditional Promotion), People (having lecturers and employees who have academic qualifications), Phisycal Evidence (having Infrastructure that supports learning activities) and Process (The process of services offered is to accommodate the process of teaching and learning activities and that can meet the needs of students). The application of the 7P concept as a university marketing strategy to increase the number of students at STAI Darussalam Kunir needs to be maximized, especially in terms of promotion